PENGARUH EFEKTIVITAS KOMITE AUDIT TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN - Juwita Hastuti; Wahyu Meiranto (Diponegoro Journal of Accounting, 2017)
The objective of the study are to examine the effect of audit committee effectiveness and the timeliness of financial reporting on manufacturing companies, which listed on Indonesia Stock Exchange in 2012-2014. The audit committee effectiveness based on DeZoort’s index that divided into four indicators such as audit committee expertise, audit committee charter, audit committee audit size, and audit committee meetingsThe population used in this study is all manufacturing companies which listed on Indonesia Stock Exchange in 2012-2014 with a total sample of 200 companies. The sampling method used in this study is purposive sampling. The data used is secondary data that are audited annual report in 2012-2014 which has been published. This study uses the technique of multiple linier regression analysis. The results showed that the audit committee expertise, audit committee size, and audit committee meetings negatively affect audit report lag. While the audit committee charter not significantly affect audit report lag.